Method, system and equipment for selecting nanocrystalline material of magnetic coupler and medium
By determining the optimal parameters of nanocrystalline materials of magnetic couplers, the problem of choosing a suitable magnetic conduction material is solved, and the radio energy transmission efficiency is improved, which is suitable for different application scenarios.
Patent Information
- Application Number
- CN202411494453.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to systematically study the impact of the magnetic characteristics and superimposed structure of nanocrystalline materials on the radio energy transmission characteristics, and select the most suitable magnetic permeable material among many nanocrystalline materials to meet the output power and efficiency of different wireless charging systems. There are difficulties in demanding.
By obtaining the parameter requirements of the magnetic coupler, the optimal stacking parameters, optimal thickness, optimal conductivity and optimal magnetic permeability of the nanocrystalline material are determined, and then the most suitable nanocrystalline material is selected. The specific steps include setting the minimum stacking system, gradually increasing the stacking coefficient F, determining the optimal stacking parameters and thickness, and calculating the optimal magnetic permeability and conductivity.
While ensuring output efficiency, it improves the transmission efficiency of the magnetic coupler and reduces the difficulty of choosing a suitable magnetic conductive material. It is suitable for different application scenarios to ensure the most suitable nanocrystal conductors for magnetic permeability, conductivity, thickness and overlap coefficient. Magnetic material.
Smart Images

Figure CN119397709A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wireless power transmission, and relates to a method, system, equipment and medium for selecting nanocrystalline materials of a magnetic coupler. Background Art
[0002] Compared with traditional wired power transmission, wireless power transmission has the advantages of safety, convenience, environmental protection and high reliability, and has good application prospects in many fields such as electric vehicles, drones, implantable medical devices, etc. At present, many studies have been conducted to improve the transmission efficiency from the aspects of control strategy, magnetic coupler design, compensation topology and magnetic conductive materials.
[0003] Magnetic conductive materials can not only strengthen the coupling between coils, but also play the role of electromagnetic shielding, so they are widely used in magnetic couplers. Nanocrystalline materials have been considered the best substitute for ferrite in recent years due to their higher initial magnetic permeability, higher saturation magnetic flux density and better ductility, and have gradually become the most commonly used magnetic conductive materials in current magnetic couplers. At present, in terms of processing technology, the use of refined crushing process and alternating seamless splicing process can reduce the eddy current loss of nanocrystals to improve transmission efficiency; there are also studies on the relationship between the thickness of single nanocrystalline nanocrystals, initial magnetic permeability, core shape and unit volume; there are also literatures proposing a new nanocrystalline ribbon core structure, which has improvements in improving efficiency and reducing magnetic leakage.
[0004] However, the influence of the magnetic properties and stacked structure of nanocrystals on the transmission characteristics of the system has not been systematically studied, nor has it considered how to select the nanocrystal material that is most suitable for a specific wireless charging system. Since nanocrystal materials can be processed into a variety of materials through mechanical crushing, heat treatment and other processes, their magnetic permeability and conductivity vary greatly. With the increase in the application of wireless charging magnetic couplers, how to select the most suitable magnetic conductive material among the many nanocrystal materials with different parameters such as magnetic permeability and conductivity according to the requirements of output power and efficiency has become a problem that needs to be solved. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and to provide a method, system, device and medium for selecting nanocrystalline materials for a magnetic coupler, which method, system, device and medium can select the most suitable nanocrystalline material.
[0006] In order to achieve the above object, the present invention adopts the following technical scheme:
[0007] In one aspect of the present invention, the method for selecting nanocrystalline materials for a magnetic coupler according to the present invention comprises:
[0008] Obtain parameter requirements for the magnetic coupler;
[0009] According to the parameter requirements of the magnetic coupler, determining the optimal lamination parameters, optimal thickness, optimal electrical conductivity and optimal magnetic permeability of the nanocrystalline material;
[0010] The nanocrystalline material of the magnetic coupler is selected according to the determined optimal stacking parameters, optimal thickness, optimal conductivity and optimal magnetic permeability.
[0011] The method for selecting nanocrystalline materials for the magnetic coupler of the present invention is further improved in that:
[0012] The process of determining the optimal lamination parameters of the nanocrystalline material according to the parameter requirements of the magnetic coupler is as follows:
[0013] Set up a minimum overlap system;
[0014] The magnetic permeability of the nanocrystalline material under different stacking coefficients F is determined by gradually increasing the magnetic permeability of the nanocrystalline material to be greater than the minimum magnetic permeability μ d The stacking parameters of the nanocrystalline material corresponding to the time are taken as the optimal stacking parameters of the nanocrystalline material.
[0015] According to the parameter requirements of the magnetic coupler, the process of determining the optimal thickness of the nanocrystalline material is:
[0016] Set the minimum thickness of nanocrystalline materials;
[0017] Establishing a finite element simulation model of a magnetic coupler, and calculating the mutual inductance M between the two coils when the two coils are facing each other under the current nanocrystalline material according to the finite element simulation model of the magnetic coupler;
[0018] Calculate the maximum magnetic flux density amplitude B based on the mutual inductance M max ;
[0019] When B s ' max , then increase the thickness of the nanocrystalline material until B s ′≥B max , taking the current thickness of the nanocrystalline material as the optimal thickness, where B s ′ is the saturation magnetic flux density of the nanocrystalline material.
[0020] The maximum magnetic flux density amplitude B is calculated according to the mutual inductance M max The process is:
[0021] Calculate the equivalent load resistance R on the AC side based on the mutual inductance M L ;
[0022] According to the AC side equivalent load resistance R L Calculate the secondary current I2;
[0023] Get the magnetic flux density amplitude B in each finite element when the current in the coil reaches I2 m_i ;
[0024] The magnetic flux density amplitude B in each finite element m_i The maximum value is taken as the maximum magnetic flux density amplitude B max .
[0025] The optimal conductivity σ' of the nanocrystalline material is:
[0026]
[0027] Among them, P out The output power P of the magnetic coupler is set out , η is the transmission efficiency of the set magnetic coupler, d is the thickness of the nanocrystalline material, M is the mutual inductance between the two coils when they are facing each other under the nanocrystalline material, ω=2πf is the angular frequency, f is the resonant frequency, r1 is the resistance of the transmitting coil, ρ represents the mass density of the nanocrystal, B m is the root mean square value of the magnetic flux density amplitude of the finite element in the nanocrystalline core, F is the stacking coefficient, k h Coefficients related to material properties.
[0028] According to the parameter requirements of the magnetic coupler, the process of determining the optimal magnetic permeability of the nanocrystalline material is:
[0029] The magnetic permeability corresponding to when the electrical conductivity of the nanocrystalline material is less than the optimal electrical conductivity is taken as the optimal magnetic permeability.
[0030] In a second aspect of the present invention, the nanocrystalline material selection system of the magnetic coupler of the present invention comprises:
[0031] An acquisition module, used for acquiring parameter requirements of the magnetic coupler;
[0032] A determination module, used to determine the optimal lamination parameters, optimal thickness, optimal electrical conductivity and optimal magnetic permeability of the nanocrystalline material according to the parameter requirements of the magnetic coupler;
[0033] A selection module is used to select the nanocrystalline material of the magnetic coupler according to the determined optimal stacking parameters, optimal thickness, optimal conductivity and optimal magnetic permeability.
[0034] The nanocrystalline material selection system of the magnetic coupler of the present invention is further improved in that:
[0035] The optimal conductivity σ' of the nanocrystalline material is:
[0036]
[0037] Among them, P out The output power P of the magnetic coupler is setout , η is the transmission efficiency of the set magnetic coupler, d is the thickness of the nanocrystalline material, M is the mutual inductance between the two coils when they are facing each other under the nanocrystalline material, ω=2πf is the angular frequency, f is the resonant frequency, r1 is the resistance of the transmitting coil, ρ represents the mass density of the nanocrystal, B m is the root mean square value of the magnetic flux density amplitude of the finite element in the nanocrystalline core, F is the stacking coefficient, k h Coefficients related to material properties.
[0038] In a third aspect of the present invention, the computer device described in the present invention includes a memory, a processor, and a computer program stored in the memory and executable on the processor, and the processor implements the steps of the nanocrystalline material selection method for the magnetic coupler when executing the computer program.
[0039] In a fourth aspect of the present invention, the computer-readable storage medium of the present invention stores a computer program, and when the computer program is executed by a processor, the steps of the method for selecting nanocrystalline materials for the magnetic coupler are implemented.
[0040] The present invention has the following beneficial effects:
[0041] The nanocrystalline material selection method, system, device and medium of the magnetic coupler described in the present invention use magnetic permeability, electrical conductivity, thickness and stacking coefficient as parameters during specific operation, and determine the optimal stacking parameters, optimal thickness, optimal electrical conductivity and optimal magnetic permeability of the nanocrystalline material according to the parameter requirements of the magnetic coupler. While ensuring the output efficiency, the transmission efficiency of the magnetic coupler is improved, and the difficulty of selecting suitable magnetic conductive materials from a large number of nanocrystalline materials is greatly reduced. In different application scenarios, the nanocrystalline magnetic conductive material with the most suitable magnetic permeability, electrical conductivity, thickness and stacking coefficient is obtained, while ensuring the output efficiency, the transmission efficiency of the magnetic coupler is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0043] Figure 1 is the equivalent circuit diagram of the magnetic coupler;
[0044] Figure 2 It is a schematic diagram of the finite element simulation model of the magnetic coupler;
[0045] Figure 3 is a flow chart of the method of the present invention;
[0046] Figure 4 This is a schematic diagram of the test magnetic coupler prototype;
[0047] Figure 5 This is a diagram showing the experimental results of a magnetic coupler prototype made of nanocrystalline magnetic conductive material selected in Example 2. DETAILED DESCRIPTION
[0048] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only an embodiment of a part of the present invention, not all embodiments, and is not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concepts disclosed in the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work should fall within the scope of protection of the present invention.
[0049] The accompanying drawings show schematic diagrams of structures according to embodiments disclosed in the present invention. These figures are not drawn to scale, and some details are magnified and some details may be omitted for the purpose of clear expression. The shapes of various regions and layers shown in the figures and the relative sizes and positional relationships therebetween are only exemplary, and may deviate in practice due to manufacturing tolerances or technical limitations, and those skilled in the art may additionally design regions / layers with different shapes, sizes, and relative positions according to actual needs.
[0050] Embodiment 1
[0051] The present invention is applicable to a symmetrical wireless charging magnetic coupler. The magnetic coupler is composed of completely identical coils and magnetic conductive materials. The coils include a transmitting coil and a receiving coil, and the magnetic conductive materials include a primary magnetic conductive material and a secondary magnetic conductive material.
[0052] The centers of the transmitting coils are aligned with each other, and the centers of the receiving coils are aligned with each other. When the two coils are facing each other, their centers are aligned.
[0053] The magnetic conductive material is a lateral nanocrystalline material. The nanocrystalline material is affected by the processing method, and has different magnetic permeability, electrical conductivity, thickness and stacking coefficient. It is suitable for wireless charging magnetic couplers with different power efficiency requirements.
[0054] refer to Figure 3 The method for selecting nanocrystalline materials for the magnetic coupler of the present invention comprises the following steps:
[0055] 1) Set the transmission efficiency η and output power P of the magnetic coupler out .
[0056] 2) Setting parameters of the magnetic coupler, wherein the parameters of the magnetic coupler include coil size, number of turns, Litz wire diameter and nanocrystalline material size, and setting the compensation topology to series-series resonant compensation.
[0057] 3) Select the nanocrystalline material with the smallest stacking coefficient F.
[0058] 4) Under the current stacking coefficient F, select the nanocrystalline material with the largest initial magnetic permeability μ.
[0059] 5) Determine whether the magnetic permeability of the current nanocrystalline material is greater than the minimum magnetic permeability μ d , when the magnetic permeability of the current nanocrystalline material is greater than the minimum magnetic permeability μ d If the optimal overlap coefficient is obtained, go to step 6); otherwise, increase the current overlap coefficient F by a preset value, and then go to step 4).
[0060] 6) Select the nanocrystalline material with the smallest thickness d.
[0061] 7) Establish a finite element simulation model of the magnetic coupler and calculate the mutual inductance M between the two coils when they are facing each other under the current nanocrystalline material.
[0062] 8) Calculate the equivalent load resistance R on the AC side based on the mutual inductance M obtained in step 7) L ;
[0063] R L =ωM+r2(1)
[0064] Among them, ω=2πf is the angular frequency, f is the resonant frequency, r2 is the receiving coil resistance, at this time the primary current I1 is equal to the secondary current I2, and P out The secondary current I2 is calculated as:
[0065]
[0066] 9) Through simulation, the current in the coil is set to I2, and the magnetic flux density amplitude B in each finite element at this time is obtained m i , where i = 1, 2, ..., n, n is the number of finite elements divided by nanocrystalline materials, and the maximum magnetic flux density amplitude B in all finite elements is recorded. max .
[0067] 10) Calculate the saturation magnetic flux density B of nanocrystalline materials s 'for:
[0068] B s ′=B s F(3)
[0069] Among them, B s is the saturation magnetic flux density of the nanocrystalline material itself;
[0070] When B s ' max , then increase d and return to step 7), otherwise, take the current thickness as the optimal thickness and go to step 11).
[0071] 11) Calculate the magnetic permeability of the nanocrystalline material that meets the target;
[0072] Calculation of the losses P on nanocrystalline materials core-loss for:
[0073]
[0074] Among them, r1 is the resistance of the transmitting coil;
[0075] The loss in the nanocrystalline material is composed of eddy current loss P e and hysteresis loss P h Composition, namely:
[0076]
[0077] Where ρ represents the mass density of nanocrystals, d represents the thickness of the nanocrystal monolayer, σ represents the conductivity of the nanocrystal material itself, and σ eq is the equivalent conductivity of the nanocrystalline core, k h Coefficient related to material properties, B m is the RMS value of the finite element magnetic flux density amplitude in the nanocrystalline core.
[0078] Then the conductivity σ' of the nanocrystalline material that satisfies the output power and output efficiency is:
[0079]
[0080] 12) When the conductivity σ<σ′, the current magnetic permeability is taken as the optimal magnetic permeability and the process goes to step 13); otherwise, the magnetic permeability μ is reduced and the process goes back to step 5).
[0081] 13) Select the best nanocrystalline material according to the conductivity σ', optimal magnetic permeability, optimal thickness and optimal stacking coefficient of the nanocrystalline material that meets the output power and output efficiency, and output it.
[0082] Embodiment 2
[0083] The specific operation process of this embodiment is as follows:
[0084] Firstly, determine the output power of the magnetic coupler to be 3kW and the transmission efficiency to be 95% and above.
[0085] The compensation topology is determined to be SS topology, the nanocrystal is a cross-shaped one, the specific parameters of the coil and the magnetic coupler are shown in Table 1, and the equivalent circuit and simulation model of the magnetic coupler are shown in Table 1. Figure 1 and Figure 2 shown.
[0086] Table 1
[0087]
[0088] Select the nanocrystalline material with an initial stacking coefficient F of 0.7, an initial magnetic permeability of 16000, and an initial thickness of 0.25 mm for simulation, and set the minimum magnetic permeability μ d is 500, and the resonant frequency f is 85000Hz. Figure 3 The process shown in the figure can obtain suitable nanocrystal parameters as shown in Table 2.
[0089] Table 2
[0090]
[0091] Through experiments, the selected nanocrystalline magnetic conductive materials were experimentally verified. The magnetic coupler prototype was tested as follows: Figure 4 The test results are as follows Figure 5 It can be seen that under the selected nanocrystalline magnetic conductive material, the output power is 3.02kW and the output efficiency reaches 95.877%, which meets the target output power and transmission efficiency of the magnetic coupler.
[0092] Embodiment 3
[0093] The nanocrystalline material selection system of the magnetic coupler of the present invention comprises:
[0094] An acquisition module, used for acquiring parameter requirements of the magnetic coupler;
[0095] A determination module, used to determine the optimal lamination parameters, optimal thickness, optimal electrical conductivity and optimal magnetic permeability of the nanocrystalline material according to the parameter requirements of the magnetic coupler;
[0096] A selection module is used to select the nanocrystalline material of the magnetic coupler according to the determined optimal stacking parameters, optimal thickness, optimal conductivity and optimal magnetic permeability.
[0097] As an embodiment of the present invention, the process of determining the optimal lamination parameters of the nanocrystalline material according to the parameter requirements of the magnetic coupler is:
[0098] Set up a minimum overlap system;
[0099] The magnetic permeability of the nanocrystalline material under different stacking coefficients F is determined by gradually increasing the magnetic permeability of the nanocrystalline material to be greater than the minimum magnetic permeability μ dThe stacking parameters of the nanocrystalline material corresponding to the time are taken as the optimal stacking parameters of the nanocrystalline material.
[0100] As an embodiment of the present invention, the process of determining the optimal thickness of the nanocrystalline material according to the parameter requirements of the magnetic coupler is:
[0101] Set the minimum thickness of nanocrystalline materials;
[0102] Establishing a finite element simulation model of a magnetic coupler, and calculating the mutual inductance M between the two coils when the two coils are facing each other under the current nanocrystalline material according to the finite element simulation model of the magnetic coupler;
[0103] Calculate the maximum magnetic flux density amplitude B based on the mutual inductance M max ;
[0104] When B s ' max , then increase the thickness of the nanocrystalline material until B s ′≥B max , taking the current thickness of the nanocrystalline material as the optimal thickness, where B s ′ is the saturation magnetic flux density of the nanocrystalline material.
[0105] As an embodiment of the present invention, the maximum magnetic flux density amplitude B is calculated according to the mutual inductance M. max The process is:
[0106] Calculate the equivalent load resistance R on the AC side based on the mutual inductance M L ;
[0107] According to the AC side equivalent load resistance R L Calculate the secondary current I2;
[0108] Get the magnetic flux density amplitude B in each finite element when the current in the coil reaches I2 m_i ;
[0109] The magnetic flux density amplitude B in each finite element m_i The maximum value is taken as the maximum magnetic flux density amplitude B max .
[0110] As an embodiment of the present invention, the optimal conductivity σ' of the nanocrystalline material is:
[0111]
[0112] Among them, P out The output power P of the magnetic coupler is set out , η is the transmission efficiency of the set magnetic coupler, d is the thickness of the nanocrystalline material, M is the mutual inductance between the two coils when they are facing each other under the nanocrystalline material, ω=2πf is the angular frequency, f is the resonant frequency, r1 is the resistance of the transmitting coil, ρ represents the mass density of the nanocrystal, B m is the root mean square value of the magnetic flux density amplitude of the finite element in the nanocrystalline core, F is the stacking coefficient, k h Coefficients related to material properties.
[0113] As an implementation mode of the present invention, the process of determining the optimal magnetic permeability of the nanocrystalline material according to the parameter requirements of the magnetic coupler is as follows:
[0114] The magnetic permeability corresponding to when the electrical conductivity of the nanocrystalline material is less than the optimal electrical conductivity is taken as the optimal magnetic permeability.
[0115] The division of modules in the embodiments of the present application is schematic and is only a logical function division. There may be other division methods in actual implementation. In addition, each functional module in each embodiment of the present application may be integrated into a processor, or may exist physically separately, or two or more modules may be integrated into one module. The above-mentioned integrated modules may be implemented in the form of hardware or in the form of software functional modules.
[0116] Embodiment 4
[0117] A computer device includes a memory, a processor, and a computer program stored in the memory and executable on the processor. When the processor executes the computer program, the steps of the method for selecting nanocrystalline materials for a magnetic coupler are implemented, for example, including: obtaining parameter requirements of a magnetic coupler; determining the optimal stacking parameters, optimal thickness, optimal conductivity, and optimal magnetic permeability of the nanocrystalline material according to the parameter requirements of the magnetic coupler; and selecting the nanocrystalline material for the magnetic coupler according to the optimal stacking parameters, optimal thickness, optimal conductivity, and optimal magnetic permeability obtained by the determination. The memory may include a memory, such as a high-speed random access memory, and may also include a non-volatile memory, such as at least one disk memory, etc. The processor, the network interface, and the memory are interconnected through an internal bus, and the internal bus may be an industrial standard architecture bus, a peripheral component interconnection standard bus, an extended industrial standard architecture bus, etc. The bus may be divided into an address bus, a data bus, a control bus, etc. The memory is used to store programs. Specifically, the program may include a program code, and the program code includes computer operation instructions. The memory may include a memory and a non-volatile memory, and provide instructions and data to the processor.
[0118] Embodiment 5
[0119] A computer-readable storage medium stores a computer program, and when the computer program is executed by a processor, the steps of the method for selecting nanocrystalline materials for a magnetic coupler are implemented, for example, including: obtaining parameter requirements of a magnetic coupler; determining the optimal stacking parameters, optimal thickness, optimal conductivity, and optimal magnetic permeability of the nanocrystalline material according to the parameter requirements of the magnetic coupler; and selecting the nanocrystalline material of the magnetic coupler according to the determined optimal stacking parameters, optimal thickness, optimal conductivity, and optimal magnetic permeability. Specifically, the computer-readable storage medium includes, but is not limited to, for example, volatile memory and / or non-volatile memory. The volatile memory may include a random access memory (RAM) and / or a cache memory, etc. The non-volatile memory may include a read-only memory (ROM), a hard disk, a flash memory, an optical disk, a magnetic disk, etc.
[0120] Those skilled in the art will appreciate that the embodiments of the present application may be provided as methods, systems, or computer program products. Therefore, the present application may adopt the form of a complete hardware embodiment, a complete software embodiment, or an embodiment in combination with software and hardware. Moreover, the present application may adopt the form of a computer program product implemented in one or more computer-usable storage media (including but not limited to disk storage, CD-ROM, optical storage, etc.) that include computer-usable program code.
[0121] The present application is described with reference to the flowcharts and / or block diagrams of the methods, devices (systems), and computer program products according to the embodiments of the present application. It should be understood that each process and / or box in the flowchart and / or block diagram, as well as the combination of the processes and / or boxes in the flowchart and / or block diagram, can be implemented by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, a special-purpose computer, an embedded processor, or other programmable data processing device to generate a machine, so that the instructions executed by the processor of the computer or other programmable data processing device generate instructions for implementing the processes in the flowchart and / or block diagram. Figure 1 A process or multiple processes and / or boxes Figure 1 A device that provides the functions specified in a block or multiple blocks.
[0122] These computer program instructions may also be stored in a computer-readable memory capable of directing a computer or other programmable data processing device to operate in a specific manner, so that the instructions stored in the computer-readable memory produce an article of manufacture comprising an instruction device, which implements the process Figure 1 A process or multiple processes and / or boxes Figure 1 A function specified in one or more boxes.
[0123] These computer program instructions can also be loaded onto a computer or other programmable data processing device so that a series of operating steps are executed on the computer or other programmable device to produce a computer-implemented process, thereby providing instructions for implementing the process. Figure 1 A process or multiple processes and / or boxes Figure 1 The steps for the functions specified in one or more boxes.
[0124] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for selecting nanocrystalline materials for a magnetic coupler, characterized in that: include: Obtain parameter requirements for the magnetic coupler; According to the parameter requirements of the magnetic coupler, determining the optimal lamination parameters, optimal thickness, optimal electrical conductivity and optimal magnetic permeability of the nanocrystalline material; The nanocrystalline material of the magnetic coupler is selected according to the determined optimal stacking parameters, optimal thickness, optimal conductivity and optimal magnetic permeability.
2. The method for selecting nanocrystalline materials for a magnetic coupler according to claim 1, characterized in that: The process of determining the optimal lamination parameters of the nanocrystalline material according to the parameter requirements of the magnetic coupler is as follows: Set the minimum overlap factor; The magnetic permeability of the nanocrystalline material under different stacking coefficients F is determined by gradually increasing the magnetic permeability of the nanocrystalline material to be greater than the minimum magnetic permeability μ d The stacking parameters of the nanocrystalline material corresponding to the time are taken as the optimal stacking parameters of the nanocrystalline material.
3. The method for selecting nanocrystalline materials for a magnetic coupler according to claim 1, characterized in that: The process of determining the optimal thickness of the nanocrystalline material according to the parameter requirements of the magnetic coupler is: Set the minimum thickness of nanocrystalline materials; Establishing a finite element simulation model of a magnetic coupler, and calculating the mutual inductance M between the two coils when the two coils are facing each other under the current nanocrystalline material according to the finite element simulation model of the magnetic coupler; Calculate the maximum magnetic flux density amplitude B based on the mutual inductance M max ; When B s ' max , then increase the thickness of the nanocrystalline material until B s ′≥B max , then the current thickness of the nanocrystalline material is taken as the optimal thickness, where B s ′ is the saturation magnetic flux density of the nanocrystalline material. 4. The method for selecting nanocrystalline materials for a magnetic coupler according to claim 3, characterized in that: The maximum magnetic flux density amplitude B is calculated according to the mutual inductance M max The process is: Calculate the equivalent load resistance R on the AC side based on the mutual inductance M L ; According to the AC side equivalent load resistance R L Calculate the secondary current I2; Get the magnetic flux density amplitude B in each finite element when the current in the coil reaches I2 m_i ; The magnetic flux density amplitude B in each finite element m_i The maximum value is taken as the maximum magnetic flux density amplitude B max .
5. The method for selecting nanocrystalline materials for a magnetic coupler according to claim 1, characterized in that: The optimal conductivity σ' of the nanocrystalline material is: Among them, P out The output power P of the magnetic coupler is set out , η is the transmission efficiency of the set magnetic coupler, d is the thickness of the nanocrystalline material, M is the mutual inductance between the two coils when they are facing each other under the nanocrystalline material, ω=2πf is the angular frequency, f is the resonant frequency, r1 is the resistance of the transmitting coil, ρ represents the mass density of the nanocrystal, B m is the root mean square value of the magnetic flux density amplitude of the finite element in the nanocrystalline core, F is the stacking coefficient, k h Coefficients related to material properties.
6. The method for selecting nanocrystalline materials for a magnetic coupler according to claim 1, characterized in that: The process of determining the optimal magnetic permeability of the nanocrystalline material according to the parameter requirements of the magnetic coupler is as follows: The magnetic permeability corresponding to when the electrical conductivity of the nanocrystalline material is less than the optimal electrical conductivity is taken as the optimal magnetic permeability.
7. A nanocrystalline material selection system for a magnetic coupler, characterized in that: include: An acquisition module, used for acquiring parameter requirements of the magnetic coupler; A determination module, used to determine the optimal lamination parameters, optimal thickness, optimal electrical conductivity and optimal magnetic permeability of the nanocrystalline material according to the parameter requirements of the magnetic coupler; A selection module is used to select the nanocrystalline material of the magnetic coupler according to the determined optimal stacking parameters, optimal thickness, optimal conductivity and optimal magnetic permeability.
8. The nanocrystalline material selection system for a magnetic coupler according to claim 7, characterized in that: The optimal conductivity σ' of the nanocrystalline material is: Among them, P out The output power P of the magnetic coupler is set out , η is the transmission efficiency of the set magnetic coupler, d is the thickness of the nanocrystalline material, M is the mutual inductance between the two coils when they are facing each other under the nanocrystalline material, ω=2πf is the angular frequency, f is the resonant frequency, r1 is the resistance of the transmitting coil, ρ represents the mass density of the nanocrystal, B m is the root mean square value of the magnetic flux density amplitude of the finite element in the nanocrystalline core, F is the stacking coefficient, k h Coefficients related to material properties.
9. A computer device comprising a memory, a processor, and a computer program stored in the memory and executable on the processor, characterized in that: When the processor executes the computer program, the steps of the method for selecting nanocrystalline materials for a magnetic coupler according to any one of claims 1 to 6 are implemented.
10. A computer-readable storage medium storing a computer program, characterized in that: When the computer program is executed by a processor, the steps of the method for selecting nanocrystalline materials for a magnetic coupler according to any one of claims 1 to 6 are implemented.